Advokasi Kebijakan Rumah Deret di Tamansari Kota Bandung: Koalisi dan Strategi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Policy advocacy in Tamansari, Bandung City, reflects the struggle of local communities in maintaining their rights to living space amidst the pressures of modernization and urban development. The area faces challenges such as land tenure conflicts, gentrification, and evictions, which raises the need for an inclusive and equitable policy approach. Advocacy is carried out through community empowerment, collaboration with civil society organizations, and support from various parties, including academics and NGOs. The research method used in this study is qualitative with data collection techniques from interviews and documentation studies. The results of this policy advocacy show that the advocacy process emphasizes the importance of community participation in decision-making, policy transparency, and a balance between development needs and the protection of local residents' rights. The Tamansari case study provides important lessons on effective advocacy strategies in the context of urbanization and land conflicts, while also offering a model for a collaboration-based approach to creating sustainable and inclusive policies.